Socio-economics of the Visayan sea fisheries sector focus on marketing and credit - Hernando, Christine Mae D. (Danyag :the UPV journal of humanities and social sciences, 2005)
"The study reviews current policy and legal framework for fisheries marketing and credit; describes existing market and credit arrangements for economic activities of municipal and commercial fishermen, and their implications on livelihood and resource utilization and management; and, recommends appropriate policies and other measures to improve marketing and access to credit for the fisheries sector of the Visayan Sea."